Kisscut ebook - Slaughter, Karin (Grant County, 2009)
The second book in the acclaimed Grant County Series from Karin Slaughter, the New York Times bestselling author of Pieces of Her. "Karin Slaughter is a fearless writer. She takes us to the deep, dark places other novelists don't dare to go. Kisscut will cement her reputation as one of the boldest thriller writers working today." —Tess Gerritsen, author of The Apprentice In this chilling follow-up to Blindsighted, Sara Linton, her ex-husband, police chief Jeffrey Tolliver, and detective Lena Adams are caught in an evil web involving a young girl who commits suicide by forcing a cop to shoot her. Shouldering the political aftermath, Jeffrey struggles to understand the victim's desperation. So does Sara, the girl's pediatrician and now her coroner, who soon discovers that the suicide was linked to a brutal crime—one far more terrifying than anyone could have imagined. Yet neither Jeffrey nor Sara know that their colleague, Lena, may unwittingly harbor the truth as she finds herself drawn to a young man who might hold the answers—and Lena's future—in his hands.